A new methodological approach to Islamic theology: with special reference to Muhammad Farid Wajdi - Abdul Rahim, Adibah (2006)
Islamic theology had undergone through several phases of development starting from the classical period of Prophet Muhammad (p.b.u.h) until late 19th and 20th centuries. Under the impact of rationalism and scientific development, the discussion of intellectual issues refected on the importance of scientific, analytical, and rational argumentations. Therefore, Muslims have been posing a new challenge to the study of theology. Numbeers Muslim modernists had raised their intellectual response to interpret Islamic thought in the light of modern knowledge. In their opinion, the task of reinterpretation is necessary to make Islam releavnt and sensitive to the changing circumstances. This phenomenon is referred to the efforts of renewal of ilm al kalam as a means of advancing a modern theological agenda. It is at this juncture, the author tries to expose the approach of Muhammad Farid Wajdi (d 1954), an Egyptian modernist who felt the need for a pardigm shfit in disseminating the message of Islam. His emphasis was that scientific discoveries and rational truths were not in conflict with Islam, thus, tying to fond points of agreement between religion and science. Such a methodology may be able to provide an alternative to the classical method used in theology. In this regard, this paper aims at exploring how Wajdi viewed the scientific and rational methdological in his attitude to theological matters, and how far had he being influenced by the Western rationalsm.